Influence of plant-based ingredients on the sensory and physicochemical indicators of salad dressing - Dudarev, Igor (Kyiv : NUHT, 2023)
A healthy lifestyle and consumption of healthy food is becoming widespread. Scientists and manufacturers pay attention to the development of innovative low-calorie food from plant-based raw materials with low fat content. Mayonnaise, which is a high-fat and high-calorie food, is the most popular salad dressing. Recipe development for mayonnaise analogues, which do not contain animal-based ingredients and are also enriched with useful nutrients, is extremely relevant. The purpose of the research is to determine the influence of plant-based ingredients on the sensory and physicochemical indicators of salad dressings and optimize their recipes. The linear programming method was used to optimize the recipes. The methods of sensory analysis and expert method were used to determine sensory properties and quality of the developed salad dressings. The weighting coefficients of the sensory indicators of bean salad dressings were determined. According to experts’ opinion, consistency, appearance and taste are the most important sensory indicators of salad dressings. The recipes of salad dressings were optimized by the content of protein, fat and carbohydrates. The developed salad dressings contain common beans, oat milk, freeze-drying fruit and vegetable powders, chicory paste. Plant-based ingredients enriched salad dressings with useful nutrients and provided them with high sensory properties. The developed salad dressings have uniform and thick purée texture, and pleasant taste and aroma. The physicochemical indicators of salad dressings were determined, in particular titratable acidity, fat and moisture content. The developed salad dressings expand the range of products from plant-based raw materials and can be positioned as healthy food. They can be used as low-calorie and low-fat analogues of mayonnaise.
Keywords: beans; salad dressing; oat milk; chicory; freeze-dried plant powder